2015
DOI: 10.1080/01919512.2015.1045059
|View full text |Cite
|
Sign up to set email alerts
|

Can Dentin Surfaces Be Bonded Safely With Ozone and Boric Acid?

Abstract: The aim of this study is to evaluate the effect of different cavity disinfectants on shear bond strength. In this study, 60 caries-free human molar teeth were used. Smooth dentin surfaces were revealed by cutting occlusal enamel and a standard smear layer was obtained by using 600-grid sandpaper. Specimens were randomly assigned to four groups according to the disinfectant used: Group 1: Control (no disinfectant); Group 2: Ozone; Group 3: Chlorhexidine, Group 4: Boric acid. Specimens were bonded using S3 Plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Most of the studies reported results on the application of cavity disinfectant agents such as chlorhexidine [ 12 , 13 , 14 , 15 , 16 , 17 , 23 , 24 , 26 , 27 , 36 , 39 , 42 , 53 , 56 , 57 , 61 , 62 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 73 , 75 , 77 , 79 , 81 , 86 , 87 , 88 , 90 , 91 , 98 , 100 , 102 , 103 , 104 , 105 , 111 , 113 , 122 , 123 , 124 , 126 , 128 , 132 , 133 , 134 , 135 , 137 , 142 , 143 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies reported results on the application of cavity disinfectant agents such as chlorhexidine [ 12 , 13 , 14 , 15 , 16 , 17 , 23 , 24 , 26 , 27 , 36 , 39 , 42 , 53 , 56 , 57 , 61 , 62 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 73 , 75 , 77 , 79 , 81 , 86 , 87 , 88 , 90 , 91 , 98 , 100 , 102 , 103 , 104 , 105 , 111 , 113 , 122 , 123 , 124 , 126 , 128 , 132 , 133 , 134 , 135 , 137 , 142 , 143 ,…”
Section: Resultsmentioning
confidence: 99%
“…The use of ozone as a cavity disinfectant was reported in five of the included studies [ 26 , 48 , 93 , 133 , 143 ]. Garcia et al [ 93 ] and Ercan et al [ 133 ] did not report a decrease in bond strength regarding restorations performed in ozone disinfected cavities. However, Rodrigues et al [ 48 ] reported a decrease in bond strength when the ozone was either used after or before the phosphoric acid application, describing a higher decrease in the latter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations